TRANSFORMASI PENDAPATAN NASIONAL INDONESIA DALAM PERSPEKTIF EKONOMI MAKRO SYARIAH DI ERA DIGITAL - Susi Rahmadani; Khairunisa Alisya Hasibuan; Rizki Simanullang; Ahmad Wahyudi Zein (INTERNATIONAL, Journal of Sharia Business Management, 2025)
This study aims to analyze the transformation of Indonesia’s national income from the perspective of Islamic macroeconomics in the digital era, which is characterized by the development of financial technology, the digitalization of the real sector, and changes in consumption patterns. The study employs a qualitative descriptive approach by reviewing academic literature, macroeconomic data, and relevant Islamic economic policies. The findings indicate that economic digitalization provides significant opportunities to increase national income through production efficiency, the expansion of Islamic financial inclusion, and the optimization of economic instruments based on justice values. From the Islamic macroeconomic perspective, national income growth is not only measured by increased output but also by fair income distribution, blessings, and social welfare. A digital economy aligned with Sharia principles can strengthen the MSME sector, promote productive zakat, and reduce economic inequality. However, challenges such as the digital divide, low Islamic economic literacy, and regulatory constraints remain major obstacles. Therefore, synergy between the government, Islamic financial institutions, and digital economic actors is essential to achieve sustainable and equitable national income growth in accordance with Islamic economic principles.